2023
DOI: 10.1002/solr.202201112
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Progress in Lead‐Free Halide Double Perovskite Solar Cells

Abstract: Lead-based metal halide perovskites have brought a revolution in photovoltaics in the last few years with a dramatic increase in the power conversion efficiency (PCE) from 3.8% in 2009 to 25.7% in 2022. [1,2] The incredible PCE improvement is mainly due to their remarkable optical and electrical properties, including suitable and tunable direct bandgap, high absorption coefficient, small exciton binding energy, long carrier diffusion length and lifetime, high carrier mobility, high defect tolerance, etc. [3][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 110 publications
(285 reference statements)
0
38
0
Order By: Relevance
“…The nontoxic double perovskites under consideration exhibit promising potential as photovoltaic absorbers, with the aim of replacing APbX 3 in halide perovskite solar cells. [43][44][45][46][47][48] Furthermore, these materials are being proposed as potential alternatives for various optoelectronic applications, including X-ray detectors, thermal neutral scintillators employed in nuclear monitoring applications, white emitting phosphors, and ultraviolet detectors. [49][50][51][52] HDP compounds have been successfully synthesized and observed in the historical world since the beginning of the 1970s.…”
Section: Introductionmentioning
confidence: 99%
“…The nontoxic double perovskites under consideration exhibit promising potential as photovoltaic absorbers, with the aim of replacing APbX 3 in halide perovskite solar cells. [43][44][45][46][47][48] Furthermore, these materials are being proposed as potential alternatives for various optoelectronic applications, including X-ray detectors, thermal neutral scintillators employed in nuclear monitoring applications, white emitting phosphors, and ultraviolet detectors. [49][50][51][52] HDP compounds have been successfully synthesized and observed in the historical world since the beginning of the 1970s.…”
Section: Introductionmentioning
confidence: 99%
“…; M = Ag + , K + , Li + ; M' = Sb 3+ , In 3+ or Bi 3+ and X = I À , Br À or Cl À ) double perovskites have become an object of significant interest due to their environmental and structural stability, low toxicity, defect tolerance, and exceptional optoelectronic properties. [1][2][3][4][5][6] These qualities have made them increasingly popular in applications such as solar cells, X-ray detectors, photodetectors, and photocatalysts. [7][8][9][10] Achieving high-performance for these applications often requires the use of high-quality perovskite single crystals (SCs).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the exploration of inorganic lead-free perovskite materials is of great significance for the future of solar cell technology. Studies have shown that all-inorganic non-lead double perovskite structures A 2 B + B 3+ X 6 (double perovskite) and A 2 B 4+ X 6 (vacancy-ordered double perovskite) could be used to solve the above problems. , However, the double perovskite has the problem of too sizable a direct or indirect bandgap, showing lower photoelectric conversion efficiency. Ion doping is an effective strategy to improve perovskite properties. , Anion mixing on the X-site has been shown to significantly improve both the photoelectric performance and the stability of perovskite. The synthesized Ti-based halide perovskite, Cs 2 TiI x Br 6– x , has tunable bandgaps between 1.0 and 1.8 eV for PV applications . Zheng and colleagues successfully prepared a series of lead-free Rb 2 ZrCl 6– x Br x double perovskite nanocrystals with excellent crystallinity and explored the influence of mixed halogens on optical properties.…”
Section: Introductionmentioning
confidence: 99%